A case study of the research careers of women academics: constraints and enablements - Obers, Nöelle Marie Thérèse (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2013)
The purpose of this research is to investigate constraints that women academics experience in their research careers and how enablements, particularly in the form of mentoring relationships and support structures, can impact on their research career development in the context of the new knowledge economy of Higher Education. The research was a case study of one South African Institution and used a mixed method approach. Social realism underpinned the research. Data was collected and analysed within the spheres of structure, culture and agency, using critical discourse analysis, interpretation and abstraction strategies. I investigated how women researchers understand and experience career success and what they perceive and experience as enablements and constraints to their research careers. Institutional support structures and cultures were examined with a focus on the role of the Head of Department. I explored mentoring and questioned whether the agency of women academics is empowered by mentoring and supportive structures to overcome constraints to their research productivity and the development of their careers. Gender-based issues of inequity, low self-esteem and accrual of social capital appear to be the underlying factors affecting how women perform in the research arena and advance within the institution. It was found that mentoring is a generative mechanism that has a favourable impact on women academics as it enables them to overcome obstacles to research productivity and career advancement.
Keywords: Career success -- Research; Women college teachers; Women in higher education; Sex discrimination in higher education